An advanced LVRT controlled DSCC-STATCOM for reactive power compensation - Rashmi Sharma; Vijay H. Makwana (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This article focuses on the control of STATCOM for the improvement of reactive power compensation during grid faults and unbalanced load. The problem encountered with convectional voltage source converter based STATCOM for reactive power management and capacitor voltage balancing during grid faults are analyzed and its operational limitations are studied. To remove the above problems, an adaptive low voltage ride through control technique based modular double star cascaded converter (DSCC) STATCOM is proposed. In this dynamic control, the positive reactive currents and negative reactive currents are separately controlled for reactive power management and a zero (Vo) sequence voltage is inserted for the management of active power. This advanced control method effectively balances the submodule capacitor voltage within its prescribed limits by managing the equal distribution of active power between converter legs and provides dynamic reactive power management during grid faults. The effectiveness of the DSCC-STATCOM, with proposed control method is verified using MATLAB/Simulink software-based simulations under single line to ground fault and unbalanced load.